Broadband Dielectric Spectroscopy of Cell Cultures - Bao, Xiue; Ocket, Ilja; Bao, Juncheng; Doijen, Jordi; Zheng, Ju; Kil, Dries; Liu, Zhuangzhuang; Puers, Bob; Schreurs, Dominique; Nauwelaers, Bart (IEEE transactions on microwave theory and techniques, 2018)
Broadband dielectric spectroscopy measurements of biological materials within RF/microwave range can reveal cellular information, which is of important value in biological and medical researches. Here, we present a platform that combines a miniaturized coplanar waveguide (CPW) transmission line (TL) sensor and a special CPW-fed interdigitated capacitor (IDC), which allows us to measure the complex permittivity of cell cultures from 300 kHz to 50 GHz. The CPW-TL and CPW-IDC sensors are integrated with an SU-8 microfluidic channel, enabling measurements of microliter or even nanoliter volumes of liquids and suspensions. Due to the accurate alignment of the SU-8 polymer and the reliable liftoff fabrication procedure, we are able to minimize the measurement errors caused by the sensors' dimension tolerance. To ensure accurate complex permittivity extraction of the tested material, related calibrations and deembedding processes are explained. With the measurement of deionized water as a validation, the platform is used to measure the complex permittivity of both a yeast cell culture and a mammalian cell culture. We elaborate on the interesting findings and discuss future possibilities.